Ethanol reduces ripening of 'Royal Gala' apples stored in controlled atmosphere - WEBER,ANDERSON (2016)
This work aims at evaluate ethanol effect of acetaldehyde application in post-storage quality of 'Royal Gala' apples maintenance, and to compare them with consolidated storage techniques. Thus two experiments were performed during the years of 2008 and 2009. In the first experiment (2008), the application of ethanol, acetaldehyde or 1-MCP and ethylene scrubbing were tested. Fruits were stored in controlled atmosphere (CA) with 1.0kPa O2 and 2.0kPa CO2 at 0.5°C. In the second experiment (2009), the treatments tested were ethanol application combined or not with low relative humidity (LRH) and LRH alone. In this experiment, apples were stored in CA with 1.2kPa O2 + 2.5kPa CO2 at 0.5°C. After eight months of storage, 0.5 mL ethanol kg-1 apples month-1 or 0.25 mL acetaldehyde kg-1 apples month-1 increased mealiness, flesh browning, and decays incidence and reduced flesh firmness. In contrast, 0.3 mL ethanol kg-1 apples month-1, tested on second experiment, prevented fruit softening and decreased ACC oxidase activity and ethylene production. Although lower relative humidity was not efficient in maintaining post-storage quality, it enhanced the positive effect of ethanol application at 0.3 mL kg-1 apples month-1.